NURSE'S DRUG PRECAUTIONS AWARENESS - S. Rahimi; A. Seyyed-rasouli (Iran University of Medical Sciences, 2004)
Undoubtedly, being aware of drug precautions in one of the most prominant responsibilities of nurses'. Good quality nursing care depends highly on the level of nurses' knowledge about drugs. So, in order to determine nurses' knowledge about drugs, a descriptive-analytic survey was conducted, in which data were collected by questionnaires. Through an easy and non-randomized sampling method 100 nurses were involved in this study. As the results showed drug precautions awareness among nurses were weak (18%), average (77%) and good (5%). Furthermore, a statistically meaningful relation was found between the mean score of nurses' awareness, patients' safety and therapeutic dosages of drugs (P= 0.001). Conclusively, the results showed the depth of educational needs of nurses in relation with drug precautions, specially, on factors related to maintaining right therapeutic dosages. Planning in service education in relation with drugs is highly recommended.